MODULE OF REPRODUCTIVE HEALTH GUIDANCE IN IMPROVING UNDERSTANDING OF PUBERTY IN STUDENT’S OF JUNIOR HIGH SCHOOL 18 MAKASSAR - Musdalifah Nihaya (International Conference on Social and Islamic Studies, 2021)
The main objectives of this study are (i) to describe the needs of puberty in students of SMP Negeri 18 Makassar; (ii) Develop acceptable reproductive health guidance modules; (iii) determine whether the development of reproductive health guidance modules is effective in increasing students' understanding of puberty. This research is a research and development, Borg and Gall model. Data collection techniques used are interviews, observations, and questionnaires. The results of this study are (i) The description of the needs of puberty in SMP Negeri 18 Makassar students is in the high category due to a lack of understanding of puberty among students so that the development of reproductive health guidance modules is very necessary as one of the guidance and counseling media to improve understanding of puberty. student; (ii) The reproductive health guidance module that has been developed has been tested by 3 experts, namely psychologists, biologists, and practitioners in the field, so that it gets a scale of 4 for each expert which can be said to be suitable for use. Based on this, this module underwent various revisions. Furthermore, the acceptability of the module was tested through a small group test involving 10 students who were ready to be used in schools in helping students to improve their understanding of puberty.